Where does cumulative culture begin?: A plea for a sociologically informed perspective - Haidle, Miriam N.; Schlaudt, Oliver (Biological theory, 2020)
Recent field studies have broadened our view on cultural performances in animals. This has consequences for the concept of cumulative culture. Here, we deconstruct the common individualist and differential approaches to culture. Individualistic approaches to the study of cultural evolution are shown to be problematic, because culture cannot be reduced to factors on the micro level of individual behavior (methodological individualism, “atomism”) but possesses a dynamic that only occurs on the group level and profoundly affects the individuals (“holism”). Naive individuals, as a prerequisite of an atomistic perspective, do not exist. We address the construction of a social approach to (cumulative) culture by introducing an inevitable social embedding of the individual development of social beings. The sociological notion of “habitus” as embodied cultural capital permits us to understand social transmission of behavioral components on a very basic level, resulting in a cumulative effect. Bits of information, movement, handling of material, attitudes, and preferences below distinct functional units are acquired through transfer mechanisms simpler than emulation and imitation such as peering, participation, co-performance, or engagement with a material environment altered by group members. The search for a zero point of cumulative culture becomes as useless as the search for a zero point of culture. Culture is cumulative.